2018
DOI: 10.1177/1120672118806436
|View full text |Cite
|
Sign up to set email alerts
|

Automated gonioscopy photography for iridocorneal angle grading

Abstract: Purpose: The aim of this study is to assess the agreement between manual and automated gonioscopy for iridocorneal angle opening. Methods: The research is a cross-sectional observational study. Manual and automated gonioscopy were performed to consecutive patients in a glaucoma clinic. Iridocorneal angle opening grading was performed according to Shaffer’s classification. Automated gonioscopy was performed with NGS-1 automated gonioscope (NIDEK Co., Gamagori, Japan). The automated gonio-photos were graded by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 18 publications
1
50
2
1
Order By: Relevance
“…It enables the visualization of angle structures, through a lens or a prism. The angle structures seen with gonioscopy from posterior to anterior are: the iris root, the ciliary body band (CB), the scleral spur (SS), the pigmented and non-pigmented TM and the Schwalbe's line (SL) [3] (Figure 2).…”
Section: Gonioscopymentioning
confidence: 99%
See 4 more Smart Citations
“…It enables the visualization of angle structures, through a lens or a prism. The angle structures seen with gonioscopy from posterior to anterior are: the iris root, the ciliary body band (CB), the scleral spur (SS), the pigmented and non-pigmented TM and the Schwalbe's line (SL) [3] (Figure 2).…”
Section: Gonioscopymentioning
confidence: 99%
“…Angle closure was detected in 23.4% and in 4.3% of the 88 eyes analyzed, by manual and automated gonioscopy, respectively. Since the agreement between the two techniques was poor, the authors concluded that automated gonioscopy needs further improvements for routine clinical use [3].…”
Section: Gonioscopic Irido-corneal Angle Anatomymentioning
confidence: 99%
See 3 more Smart Citations